Characterization of sugarcane bagasse and its potential for energy generation and cellulosic pulp - Vivian, Magnos Alan; Santos, Juliana Rodrigues Siviero dos; Segura, Tiago Edson Simkunas; Silva Júnior, Francides Gomes da; Brito, José Otávio (Instituto de Ecología, A.C., 2022)
Brazil is the world's largest producer of sugarcane, from which sugar and ethanol are obtained. However, after the production process, waste remains, among which stands out the bagasse, which generates millions of tons annually. The bagasse can be used for many purposes; however, it is important to know its properties in order to make the best use of it. Thus, the present study aimed to evaluate the bagasse's physical, chemical, and anatomical properties, as well as its potential for energy generation and pulp production. The evaluations of the characteristics and potential of bagasse followed the recommendations and standards of the Brazilian Association of Technical Standards [ABNT], the Technical Association of the Pulp & Paper Industry Inc. [TAPPI], and the International Association of Wood Anatomists [IAWA]. Based on the results, a low density (0.048 g/cm3) was observed; high ash (5.8%) and extractives (5.7%) content, and low lignin content (24.5%); and fibers with moderately long length (1.60 mm), the other dimensions being compatible with eucalyptus wood; and regular anatomical quality indicators for paper production. The bagasse has a good energetic potential in nature, and the heat treatment provides a significant gain in this regard. In addition, the bagasse also has good potential for pulp production, with yields similar to those reported for eucalyptus wood, but with a higher reject content, and less viscosity and hexenuronic acids content. In general, sugarcane bagasse has interesting properties and can be better used, either for energy generation or pulp production.